In Vitro Evaluation of the Effect of Different Sandblasting Times on the Bond Strength of Feldspathic Porcelain to Composite Resin - Ebrahim Amin Salehi; Haleh Heshmat; Elham Moravej Salehi; Mohammad javad Kharazifard (Islamic Dental Association of Iran, 2013)
Background and Aim: Intraoral repair of fractured porcelain is an acceptable method to avoid replacement and therefore saving time and cost. The purpose of this study was to determine the in-vitro shear bond strengths of composite resin to feldspathic porcelain after different durations of sandblasting and to compare the effect of sandblasting with that of hydrofluoric acid (HF ).   Materials and Methods : In this in-vitro study, 40 porcelain disks were fabricated and randomly divided into 4 groups (n=10). Porcelain surface in group 1 was etched with 9.5% HF for 2 minutes. Groups 2, 3 and 4 were sandblasted with 50µm alumina particles for 5, 10 and 15 seconds, respectively. All specimens received the same silane agent, bonding agent and composite resin. The samples were subjected to 5000 thermal cycles and then underwent shear bond strength testing. The mean bond strength was analyzed with one-way ANOVA. The mode of failure was determined using stereomicroscope and scanning electron microscope. An additional porcelain sample was fabricated and prepared according to the aforementioned protocols in each group and its surface topography was observed by SEM .   Results: The mean bond strength was 15/28 (±3/64), 13/82(±4/03), 15/77(±3/94) and 16/54(±3/73) MPa in the 4 groups, respectively. There were no statistically significant differences among groups. The most common mode of failure was cohesive in porcelain. No statistically significant difference was found in SEM results of different durations of sandblasting .   Conclusion: The shear bond strength was not significantly different after various durations of sandblasting treatment. The bond strength after sandblasting was similar to that of HF. SEM showed that HF acid etching and sandblasting patterns were different .